It should increase but I’m between stays the same or increase, I’m not sure in a 100% sorry...
Answer:
Step-by-step explanation:
x² - x -6 = x² + 2x - 3x - 3*2
=x(x + 2) - 3(x + 2)
= (x + 2 )(x - 3)
![\frac{1}{x^{2}-x-6}+\frac{x}{x+2}=\frac{1}{(x +2 )(x - 3)}-\frac{x}{x + 2}\\](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bx%5E%7B2%7D-x-6%7D%2B%5Cfrac%7Bx%7D%7Bx%2B2%7D%3D%5Cfrac%7B1%7D%7B%28x%20%2B2%20%29%28x%20-%203%29%7D-%5Cfrac%7Bx%7D%7Bx%20%2B%202%7D%5C%5C)
![= \frac{1}{(x+2)(x-3)}-\frac{x(x-3)}{(x+2)(x-3)}\\\\=\frac{1-x(x-3)}{(x+2)(x-3)}\\\\=\frac{1-x^{2}+3x}{(x+2)(x-3)}\\\\](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B1%7D%7B%28x%2B2%29%28x-3%29%7D-%5Cfrac%7Bx%28x-3%29%7D%7B%28x%2B2%29%28x-3%29%7D%5C%5C%5C%5C%3D%5Cfrac%7B1-x%28x-3%29%7D%7B%28x%2B2%29%28x-3%29%7D%5C%5C%5C%5C%3D%5Cfrac%7B1-x%5E%7B2%7D%2B3x%7D%7B%28x%2B2%29%28x-3%29%7D%5C%5C%5C%5C)
Answer:
7/18
Step-by-step explanation:
21 out of 54 = 21/54 = 7/18
Answer:
2550
Step-by-step explanation:
Hope This Helps
Answer:
i tried but all i got was like 80 percent
Step-by-step explanation: